Diagnosabilities of regular networks under three-valued comparison models. (2017) - Xu, Xiang; Zhou, Shuming; Xu, Li
Under the comparison model, earlier studies (Sengupta and Rhee, 1990) introduced t / x - and t [ x ]-diagnosis strategies based on multiple-valued logic. A multiprocessor system is t / x -(respectively, t [ x ]-) diagnosable if all faulty units can be uniquely identified from syndrome provided that there are no more than t faulty units and no more than x missing (respectively, incorrect) test outcomes. In this paper, we present some determinant characterisations on t / x -diagnosability and t [ x ]-diagnosability of multiprocessor systems based on regular network.